2009
DOI: 10.1371/journal.pone.0008234
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Vascularisation and Involvement of Lyve-1+ Macrophages in the Human Onchocerca Nodule

Abstract: Onchocerciasis, caused by the filarial nematode Onchocerca volvulus, is a parasitic disease leading to debilitating skin disease and blindness, with major economic and social consequences. The pathology of onchocerciasis is principally considered to be a consequence of long-standing host inflammatory responses. In onchocerciasis a subcutaneous nodule is formed around the female worms, the core of which is a dense infiltrate of inflammatory cells in which microfilariae are released. It has been established that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 46 publications
2
37
1
Order By: Relevance
“…It was frequently reported that macrophages positive for LYVE-1 influence lymphangiogenesis. [41][42][43][44][45][46] In fact, we observed that the macrophage-like cells positive for LYVE-1 and VEGFR-3 accumulated to the granulation tissues. Furthermore, it was reported that VEGFR-1 tyrosine kinase signaling promotes lymphangiogenesis, as well as angiogenesis, indirectly via macrophage recruitment.…”
Section: Discussionmentioning
confidence: 64%
“…It was frequently reported that macrophages positive for LYVE-1 influence lymphangiogenesis. [41][42][43][44][45][46] In fact, we observed that the macrophage-like cells positive for LYVE-1 and VEGFR-3 accumulated to the granulation tissues. Furthermore, it was reported that VEGFR-1 tyrosine kinase signaling promotes lymphangiogenesis, as well as angiogenesis, indirectly via macrophage recruitment.…”
Section: Discussionmentioning
confidence: 64%
“…TAMs are critical regulators of angiogenesis and lymphangiogenesis; they express VEGFA and VEGFC and induce tip-cell formation and fusion (16,(30)(31)(32)(33). In addition, they are thought to directly contribute to lymphatic vessel formation by transdifferentiating into lymphatic endothelial cells (25,28,33,34).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that, at both sites, many of the nodules had become attached to host tissues and the majority of nodules had evidence of rapid host neovascularization. Vascularisation with both blood and lymphatic vessels is a consistent feature of O. volvulus nodule microarchitecture [50][51][52]. Whether neovascularisation is actively induced by pro-angiogenic parasite secretions [53] or is part of an innate inflammatory response to foreign material, remains to be resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Because O. lienalis mf show a cumulative increase in recruitment to the skin during the first three weeks following inoculations in SCID mice [22] extended experiments are required to determine the dynamics of mf recruitment to the skin from implanted nodules. As lymphatic growth into nodular tissue has been proffered as an exit route for mf migration into the skin [52], this process may be dependent on lymphangiogenic responses developing within implanted nodules.…”
Section: Discussionmentioning
confidence: 99%